Development Of Natural Coagulant Aid From Artocarpus Heterophyllus Seeds Starch For Landfill Leachate Treatment - Zuki, Noor Aina Mohamad (2016)
Coagulation-flocculation has been extensively used as landfill leachate treatment, prior to other methods. Al-based coagulant like polyaluminium chloride (PACl) is prominent in landfill leachate treatment, though the applications of PACl may introduce potentially toxic Al residuals into aquatic environment. As alternative, starch-based coagulants has been produced from jackfruit seeds. In comparison with PACl, JSS has a lower percentage removal of pollutants i.e. COD (10.8%), colour (15.9%), turbidity (25%) and suspended solids (7.5%). From preliminary study had ascertained that optimum pH and dosages for JSS and PACl were at pH 5 and 3000mg/L, pH 5 and 900 mg/L, respectively. Then, JSS was further studied to be used together with PAC as coagulant aid in landfill leachate treatment. Jar test result demonstrated that at optimum condition of pH 5, 600 mg/L of PACl and 500 mg/L of JSS has increased the percentage removal of COD up to 33.5%, while other parameters does not show any increment in percentage removal when compared to PACl as primary coagulant. Though PACl was more effective in overall coagulation performance, i.e. COD (2.7%), colour (93.5%), turbidity (95.6%) and suspended solids (90.3%), but under the optimization using response surface methodology (RSM), the amount of dosages used in both coagulants had reduced by 12.4% for PACl (from 600 mg/L to 523.32 mg/L) and 20% for JSS (from 500 mg/L to 400 mg/) with similar percentage removal from preliminary study. Therefore, JSS could be feasible selective coagulant aid in landfill leachate treatment, benefitted in reducing dosage of PACl used, depending on leachate condition. The overall findings had concluded that JSS as coagulant aid was fairly feasible for landfill leachate treatment in terms of supply availability, production price, coagulation performance and sustainable environment management.